Analisis Framing Literasi Digital Followers Media Kreatif pada Postingan Konten Muslim Selebriti di Akun Facebook Pojoksatu.Id - Anggrayni, Dewi; Jannah, Miftahul; Pahlevi, Herdy Ardiansyah (CV. ULIL ALBAB CORP, 2025)
The main problem faced by social media account managers of entertainment news portals is ensuring that the content produced is entertainment and a reference for followers in increasing digital literacy interest. This study will analyze celebrity news posts produced by the @pojoksatu.id channel via Facebook social media accounts for the period October-December 2024. Using a descriptive qualitative approach, researchers will focus on analyzing 100 posts of images, videos, and interactive content. This study will use framing theory to understand how social media account managers construct reality through celebrity content produced on the @pojoksatu.id account. Researchers determine indicators of public interaction and expectations towards the framing of @pojoksatu.id content by observing the number of likes, comments, and views. This data shows the interaction of followers with celebrity posts with the themes of polygamy and lifestyle, which illustrates the level of audience engagement with the content. For the polygamy theme, which recorded 3.4k likes, 88 comments, and 668k views, it is included in the Video Interactivity indicator. This content, which raises controversial issues such as polygamy, shows how the audience responds with a high level of engagement, reflecting the formation of public discourse through media framing. On the other hand, Nissa Sabyan's lifestyle theme, with 334k views, 2.3k likes, and 1.3k comments, is included in the Copywriting Poster Public Response Indicator. Although this content is static, the use of effective copywriting in the poster has succeeded in triggering a positive response and curiosity from the audience, reflecting how message framing can influence public expectations and encourage further interaction. Both show how framing theory, through word choice and narrative, shapes the way audiences view and respond to issues raised in the content. The results of this study indicate that celebrity content not only functions as entertainment, but also as an important tool for increasing digital literacy among followers, especially on widely used social media platforms. Interesting celebrity creative content posts, especially in the form of videos, get audience responses and show an interest in digital literacy towards issues surrounding celebrities on the @pojoksatu.id account. This study provides insight for followers of social media portal media in designing content framing that has an impact on followers' digital literacy so as to provide education on the latest issues surrounding celebrities.